PENERAPAN MASSAGE EFFLURAGE PADA PERAWATAN IBU POST PARTUM UNTUK MENGATASI MASALAH MENYUSUI TIDAK EFEKTIF DI RUANG DAHLIA RUMAH SAKIT BHAKTI WIRATAMTAMA SEMARANG - Fatimah, Siti; Wulaningsih, Indah (NHM PRESS, 2024)
Background: Mother's milk is the best nutritional intake that can meet all the growth and development needs of babies up to 6 months of age. Breastfeeding can provide benefits from various aspects. These various aspects include nutritional aspects, immunological aspects, psychological aspects, intelligence aspects, neurological aspects, economic aspects, and delaying pregnancy. However, during the breastfeeding process, problems are often found in the production or ejection of breast milk. One non-pharmacological therapy that can help increase the flow of breast milk and overcome the problem of ineffective breastfeeding is effleurage massage. Effleurage massage can stimulate the release of oxytocin which plays a role in the breastfeeding process. Method: Writing instruments used are observation sheets, nursing care reports, SOP procedures. Result: the problem of ineffective breastfeeding can be resolved after effleurage massage therapy, which was marked by an increase in breast milk production until the second to third day of intervention only started to see breast milk droplets coming out after the efflurage massage.